2010
DOI: 10.5005/jp-journals-10005-1070
|View full text |Cite
|
Sign up to set email alerts
|

To Evaluate Cytotoxicity of Resin-based Restorative Materials on Human Lymphocytes by Trypan Blue Exclusion Test: An in vitro Study

Abstract: The cytotoxicity of a resin-based material can be evaluated on isolated human lymphocyte. Since resin-based dental materials have been used with increasing frequency in anterior and posterior teeth restorations, the uncured resin monomers are leached out from the restorations and diffuses into the dentine and ultimately hampers the odontoblastic layers of pulp as well as gingiva. It is also reaches into the saliva and circulatory blood. The study evaluates and compares the relative cytotoxicity of resin-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The present study showed that Medental micro-hybrid composite resins elicited a slightly lower cellular inflammatory response on the 2nd and 14th days, but the vascular congestion was slightly higher on the 2nd day of implantation. As reported in culture experiments, 11,12 the difference in the cellular inflammatory responses may be related to the higher filler content in the Medental product. Ergun et al 11 discovered that the composite resins that had the highest rate of survival among the five tested composite resins was the one with the highest weight (87%) of filler content.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The present study showed that Medental micro-hybrid composite resins elicited a slightly lower cellular inflammatory response on the 2nd and 14th days, but the vascular congestion was slightly higher on the 2nd day of implantation. As reported in culture experiments, 11,12 the difference in the cellular inflammatory responses may be related to the higher filler content in the Medental product. Ergun et al 11 discovered that the composite resins that had the highest rate of survival among the five tested composite resins was the one with the highest weight (87%) of filler content.…”
Section: Discussionmentioning
confidence: 70%
“…Ergun et al 11 discovered that the composite resins that had the highest rate of survival among the five tested composite resins was the one with the highest weight (87%) of filler content. Srivastava et al 12 also reported that flowable composite resins with higher resin content showed maximum toxicity compared to nano composite resin and compomer.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…To identify the rate of living cells in the culture, different stains (trypaneblue, erythrosine, naphthalene black, diacetyl fluorescent or neutral red) are used which can enter the cell structure. In the evaluation of metabolic impairments, MTT, LDH and Alamar blue tests are primarily used [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Srivastava et al 53 evaluated the cytotoxicity of nanocomposites, flowable composites, and composite materials on human lymphocyte cells. They found that all three materials showed cytotoxic effects, and flowable composites had a higher cytotoxic effect than composites and nanocomposites.…”
Section: Cytotoxicity Studies On Resin-containing Materialsmentioning
confidence: 99%